ANALISIS NILAI TAMBAH UBI KAYU MENJADI TEPUNG MOCAF DI KABUPATEN KAMPAR, PROVINSI RIAU - Yasmin, Nazwa Azura; Nofa, Tasya; Nahda, Azah; Rahmadhani, Oktavia; Hamid, M. (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Indonesia faces a high dependency on imported wheat, despite possessing abundant local carbohydrate resources such as cassava (ubi kayu). Cassava is highly perishable and commands a low selling price in its raw form. Modified Cassava Flour (Mocaf) is a fermented cassava flour product with wheat-like characteristics, holding significant potential as an import substitute. However, in production centers like Kampar Regency, Riau, farmers have not widely adopted this processing technology. This research aims to (1) Analyze the economic value-added, value-added ratio, and profit margins from processing cassava into Mocaf flour in Kampar Regency; (2) Identify the factors influencing the value-added process, such as technology, input costs, and market access; and (3) Provide strategic recommendations for the sustainable development of the Mocaf industry. This study employs a quantitative descriptive approach using a case study method focused on a Mocaf-processing SME in Kampar Regency. Secondary data from BPS (Statistics Indonesia) and literature. Data analysis will utilize the Hayami Method to calculate value-added and a business income analysis ( ) to measure feasibility.